Relationship between duration of breast feeding and endometrial cancer: a case-control study - Zohreh Yeganeh; Zohreh Sheikhan; Parastoo Hajian; Taraneh Esteki; Malihe Nasiri; Nahid Khodakarami (Mashhad University of Medical Sciences, 2020)
Introduction: Endometrial cancer is the most common gynecologic malignancy in developed countries. The incidence of endometrial cancer is increasing in Iran. The risk of endometrial cancer is related to estrogen levels that breastfeeding reduces it. This study was performed with aim to compare breastfeeding duration in women with endometrial cancer and women without endometrial cancer. Methods: This retrospective case-control study was performed on 240 women referring to the hospitals of Shahid Beheshti University of Medical Sciences, Tehran in 2017. The case group included women with endometrial cancer and the control group was women without endometrial cancer. Data was collected by interview and completion of demographic and fertility characteristics, medical records and endometrial cancer information. Data were analyzed by SPSS (version 21) and Chi-Square, independent T-Test, Mann-Whitney and ROC curve. P< was considered statistically significant. Results: 24 women (20%) in case group and 41 women (34%) in control group reported the history of breastfeeding. The mean duration of breastfeeding in the case group was 58.58±22.19 months and in the control group were 72.61±15.38 months. The duration of breastfeeding in the case group was significantly shorter than the control group (p = 0.004). Conclusion: Women with endometrial cancer had shorter duration of breastfeeding, so breastfeeding training must be noticed as postpartum care.